Identification of hub genes and immune-related pathways in acute myeloid leukemia: insights from bioinformatics and experimental validation - Shan, Mingliang; Xu, Li; Yang, Wenzhe; Liu, Shiguo; Cui, Zhaoqing (Frontiers in Immunology, 2025)
BackgroundThis study aims to identify the hub genes and immune-related pathways in acute myeloid leukemia (AML) to provide new theories for immunotherapy.MethodsWe use bioinformatics methods to find and verify the hub gene. At the same time, we use the results of GSEA enrichment analysis to find immune-related mediators. Through Mendelian randomization(MR) analysis, on the one hand, we look for related immune cells, and on the other hand, we use it to determine the causal relationship among immune cells, immune mediators, and AML. Finally, in vitro experiments are conducted to further verify and improve the reliability and physiological functions of the hub gene and its immune-related pathways.ResultsComplement Factor D(CFD) gene is identified as the highly expressed hub gene and is positively correlated with IL-2. IL-2 is also positively correlated with CD27 on CD24+CD27+B cells, JAK/STAT, and PI3K/Akt. The latter three are positively correlated with the occurrence and development of AML.ConclusionWe conclude that CFD gene uses IL-2 as a mediator to promote the disease progression of AML by promoting the CD27 on CD24+CD27+B cells, JAK-STAT, and PI3K-Akt pathways.